Religious Disaffection and ‘Unaffiliated’ Individuals: Qualitative Approaches to the Chilean Case - Bravo-Vega, F (Springer Science and Business Media Deutschland GmbH, 2024)
The objective of this article is to explore the phenomenon of individuals without religious affiliation as a representative manifestation of the transformations within the Chilean religious field in recent decades. The theoretical framework consisted of a theoretical construction of the category ‘unaffiliated’, which is understood as a positional phenomenon that presents other ways in which individuals perceive and represent themselves beyond religious frameworks (Mallimaci and Giménez, Rev Argent Sociol 9(5):44–63, 2007; Rabbia, Estud Relig 31(3):131–155, 2017). An open and non-institutional conception of religion was used, understood as the various ways in which individuals relate to superhuman forces, interacting with a meta-empirical plane. These modes are understood within a network of relationships between human and non-human agents (Morello 2020; Frigerio, Cult Represent Soc, 12(24):51–95, 2018; Heehs 2021; Morris 2015). The methodological framework consisted of a qualitative design based on an interpretive paradigm. Through theoretical sampling, the selection criteria for participants were men and women from three metropolitan areas of Chile, aged between 25 and 45, belonging to middle and urban sectors: the La Serena-Coquimbo conurbation, the Metropolitan Region, and Greater Concepción. Among the results, we highlight the recognition of ‘unaffiliated’ categories that were situated in three regimes: cosmological (high intensity), disaffiliated (medium and low intensity), and ‘non-religious’ (null intensity). Subsequently, the notion of autonomy, understood as a transversal ideal of ‘unaffiliated’ narratives, was critically analysed. It is proposed that religiosity and ‘non-religiosity’ produced outside institutional frameworks occur over a network of relationships that we call the principle of affective relationality. Both aspects shape the uniqueness of the Chilean case. It is concluded that the ‘unaffiliated’ positions which we have explored constitute an expression of individuality in a post-secular society which has produced individuals who exist in social life as ‘hyper-actors’ under the imperative of autonomy and supported by an idea of self-sufficiency. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.